Pengaruh Kualitas E-Ticketing terhadap Kepuasan Konsumen PT ASDP Cabang Ketapang Banyuwangi - Efan Dwi Nugraha; Indah Ayu Johanda Putri; Akhmad Kasan Gupron (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The purpose of this research is to find out whether the quality of e-ticketing can provide satisfaction to consumers, what is consumer satisfaction with the services provided by e-ticketing, and to find out the effect of e-ticketing quality on consumer satisfaction at PT ASDP Ketapang Branch. The population of this study is all passengers who purchased tickets online at PT ASDP Ketapang branch, the sample used was 30 people. The data analysis techniques used are quantitative descriptive analysis techniques, simple linear regression analysis, classical assumption tests, hypothesis tests and coefficient of determination tests (R2). Based on the research results, it can be seen that the quality of e-ticketing can provide satisfaction to consumers or passengers who use ship services belonging to PT ASDP ketapang branch Banyuwangi, apart from that consumers/passengers are satisfied with the services provided by PT ASDP Ketapang branch Banyuwangi related to the existence of e-ticketing. ticketing or purchasing tickets online. Based on the calculation results, it is known that R square has a value of 0.667 or 66%. This shows the magnitude of the positive influence of E-Ticketing Quality on PT ASDP Ketapang branch , Banyuwangi (Y) is 66%, the remaining 34% is the influence of other factors.